Investigation of surface properties of various parts of Angelica sylvestris by inverse gas chromatography - Habiboglu, Melek Kubra; Isik, Birol; Cakar, Fatih (OXFORD UNIV PRESS INC, 2026)
There are nine different varieties of Angelica sylvestris plants found in Asia, America, and Europe, and all of them, especially their roots, have medicinal properties. It is important to determine the surface properties of medicinal A. sylvestris that can be easily found in nature. In this study, it was aimed to investigate the surface characteristics of the root, stem, and flower parts of the A. sylvestris. For this purpose, gas chromatography columns were prepared by separating the root, stem, and flower parts of the plant, and the surface properties were determined by the inverse gas chromatography (IGC) method. The IGC study was performed at infinite dilution with polar and non-polar solvents. Surface characteristics of different parts of the plant were determined through analysis of retention diagrams. From IGC experiments, the changes in the acidic and basic character of the parts of the plant were determined and compared with each other. As a result of this comparison, it was found that all K-D/K-A values were less than 1 and changed as flower > root > stem. [GRAPHICS] .
Keywords: ACID-BASE PROPERTIES; ADSORPTION; ALKANES; ENERGY; Biochemistry & Molecular Biology; Chemistry